ANALISIS PENDAPATAN USAHA MEUBEL ROTAN CV. PALUNESIA COLLECTION DI KOTA PALU - Moh Fahrul; Arifuddin Lamusa; Muh Alfit A. Laihi (Universitas Tadulako, 2022)
Rattan furniture is one of the Micro, Small and Medium Enterprises in Palu City, Central Sulawesi Province, Rattan Furniture Business is one of the businesses that is quite competitive, the problems that are often faced by Rattan Furniture Businesses are generally the availability of raw materials, technology, labor, capital and marketing which then affects the income of the Rattan Furniture Business in Palu City. Research goal is to know the income obtained by enterprise of furniture rattan CV. Palunesia Collection in Palu City. The research conducted at R.E Martadinata. The research conducted in the furniture CV. Palunesia Collection from February to April 2020. Determinations of respondents conducted by using the purposive method. Data used was Analysis Income. Prodct furniture rattan CV. Palunesia Collection consists 4 types item furniture that keong chairs, mersi chairs, sedan chairs, and kipas chairs. Research results indicate the income earned by furniture CV. Palunesia Collection in Palu City is Rp. 14.853.618.